AI-Powered Educational Videos as an Innovative Approach to Increase Knowledge of Stunting Prevention among Adolescent Girls - Wieda Widyatry Qarragyta; Asep Nidzar Faijurahman; Arief Gustiar R; Sri Yekti Widadi (Jurnal Penelitian Pendidikan IPA, 2025)
Stunting remains a public health problem in Indonesia with long-term impacts on health, education, and productivity. Prevention efforts starting from adolescent girls are crucial because mothers' knowledge influences the risk of stunting in the next generation. This study aimed to assess the effectiveness of Artificial Intelligence (AI)-based educational videos in improving adolescent girls' knowledge about stunting prevention. A quasi-experimental pretest–posttest design was conducted on 72 respondents, selected proportionally from the student population. The intervention took the form of education through AI-based video media, with respondents' knowledge measured before and after the intervention, and then analyzed using paired statistical tests. The results showed that the average knowledge score increased significantly from moderate to high after the intervention (p < 0.05). These findings support previous studies that confirm the effectiveness of digital media and AI in improving adolescent health literacy. In conclusion, AI-based video media are effective in increasing adolescent girls' knowledge about stunting prevention and have the potential to be integrated into health education programs as a preventive strategy to reduce the prevalence of stunting in Indonesia.